Acidified glycerol as a one-step efficient green extraction and preservation strategy for anthocyanin from blueberry pomace: New insights into extraction and stability protection mechanism with molecular dynamic simulation. (1st October 2022) - Fu, Xizhe; Du, Yinglin; Zou, Ligen; Liu, Xingquan; He, Yihan; Xu, Yanqun; Li, Li; Luo, Zisheng
Highlights: Acidic glycerol is an efficient and green alternative for anthocyanin extraction. Acidic glycerol showed higher protective effect on extracted anthocyanin. Hydrogen bond number and lifetime account for better performance of glycerol. Interactions between anthocyanin and different solvents were compared. 10 Anthocyanins were identified in glycerol extract of blueberry pomace. Abstract: In present work, green and efficient glycerol solvent system was coupled with pulse-probe ultrasonication for one-step extraction and preservation of anthocyanin from blueberry pomace. Under optimal conditions (40 min, 174 W, 18.6 mL/g, 20% of glycerol fraction), extraction yield was 23.07 ± 0.09 mg C3GE/g DW. The extracted anthocyanins were characterized by UPLC-Triple-TOF/MS and 10 anthocyanins compounds were tentatively identified. Stability of anthocyanins influenced by solvents were evaluated in varying temperature, pH and light exposure conditions, demonstrating higher stability of anthocyanins in glycerol solvent system than methanol one. Furthermore, mechanism of high efficiency extraction and stability of anthocyanin using glycerol were investigated by quantum chemical calculation with molecular dynamic simulation. Larger solvent accessible surface area (127.16 nm 2 ), hydrogen bonds number (228.16) and hydrogen bonds lifetime (4.35 ps), and lower intermolecular interaction energy (-1080.48 kJ/mol) between anthocyanin and glycerol were responsible for better extraction and preservation of anthocyanins using glycerol system.